2012
DOI: 10.1073/pnas.1121120109
|View full text |Cite
|
Sign up to set email alerts
|

MED12 mutations link intellectual disability syndromes with dysregulated GLI3-dependent Sonic Hedgehog signaling

Abstract: Recurrent missense mutations in the RNA polymerase II Mediator subunit MED12 are associated with X-linked intellectual disability (XLID) and multiple congenital anomalies, including craniofacial, musculoskeletal, and behavioral defects in humans with FG (or Opitz-Kaveggia) and Lujan syndromes. However, the molecular mechanism(s) underlying these phenotypes is poorly understood. Here we report that MED12 mutations R961W and N1007S causing FG and Lujan syndromes, respectively, disrupt a Mediator-imposed constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…GLI3, a TF whose activity is regulated by SHH signaling, was shown earlier by the same group to bind directly to MED12 (20). Zhou et al (6) realized that several of the phenotypes of the FG and Lujan syndromes, such as corpus callosum defects, are also observed in patients with mutations in GLI3. Consequently, they analyzed the impact of the FG and Lujan MED12 mutations on transcription of genes activated by SHH signaling and on the association of CDK8 with several promoters through ChIP assays.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…GLI3, a TF whose activity is regulated by SHH signaling, was shown earlier by the same group to bind directly to MED12 (20). Zhou et al (6) realized that several of the phenotypes of the FG and Lujan syndromes, such as corpus callosum defects, are also observed in patients with mutations in GLI3. Consequently, they analyzed the impact of the FG and Lujan MED12 mutations on transcription of genes activated by SHH signaling and on the association of CDK8 with several promoters through ChIP assays.…”
mentioning
confidence: 99%
“…Consequently, they analyzed the impact of the FG and Lujan MED12 mutations on transcription of genes activated by SHH signaling and on the association of CDK8 with several promoters through ChIP assays. They find that GLI3 target genes, but not genes regulated by several other signal transduction pathways, are greatly overexpressed in response to SHH signaling in cells from patients with FG and Lujan syndrome (6). ChIP assays showed that CDK8 was depleted at GLI3-regulated promoters, but not at other promoters.…”
mentioning
confidence: 99%
See 3 more Smart Citations